HP57 : Peripheral nerve involvement in AL Amyloidosis : A long prospective follow up study. (March 2022) - Bountziouka, C.; Kastritis, E.; Schmelz, M.; Theodorakakou, F.; Fotiou, D.; Kokotis, P.
Abstract : The presence of the peripheral neuropathy in AL amyloidosis and correlation with the course of the disease. Methods: A prospective study of 53 patients with newly AL amyloidosis (28 male, mean age 62 years ± 10) and 21 age and gender matched healthy controls underwent neurological examination with Neurological Symptom Score, Neurologic Impairment Score, Nerve Conduction Study, Quantitative Sensation Test (QST) and skin biopsy at the lower leg by an expert Neurologist. Small fiber neuropathy (SFN) diagnosis was based on abnormality of at least two among clinical signs, intraepidermal nerve fiber density (IEFND) and QST results. Results: Among patients 61.54% were diagnosed with both large and small fiber neuropathy (LSFN), 13.2% with only SFN, 15.09% with only LFN and 9.43% without neuropathy. The type of LFN was axonal sensory or sensorimotor neuropathy. The gender didn't altered the presence or the type of neuropathy. Ten out of 52patients died the first 6 months after the diagnosis. There was not statistically significant prevalence in the type of neuropathy among the above patients and the others, but the patients with SFN trend to have shorter survival. We did not find yet any correlation between IEFND and survival, but the follow up of the patients is continued. Conclusion: In AL amyloidosis the most common type of neuropathy is LSFN, without clear difference among men and women. It seems that SFN could serve as a prognostic factor of survival.